1993
DOI: 10.1017/s0031182000074758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of qinghaosu (artemisinin) and its derivatives on experimental cutaneous leishmaniasis

Abstract: We have investigated the effect of qinghaosu (QHS, artemisinin) and its derivatives on Leishmania major replication in vitro and on the disease development in mice infected with L. major. Artemisinin is effective against promastigotes in vitro, with an ED50 (50% effective dose) at 7.5 x 10(-7) M. Both artemisinin and artemether are leishmanicidal for amastigotes in infected murine macrophages in vitro, with ED50 at 3 x 10(-5) M and 3 x 10(-6) M respectively. These compounds have no effect on the viability of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
2
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 2 publications
3
40
2
10
Order By: Relevance
“…Artemisinins inhibited 90% of parasite growth at 46.5 M to 50.8 M for T. cruzi and 44.8 M to 49.6 M for T. brucei rhodesiense. The IC 50 values for the trypanosomes are comparable to those obtained with L. donovani promastigotes, which have previously been shown to be susceptible to artemisinin compounds in vitro and in vivo (1,15,23). Similar results were also obtained in drug IC 50 determinations for Leishmania and Trypanosoma spp.…”
supporting
confidence: 83%
“…Artemisinins inhibited 90% of parasite growth at 46.5 M to 50.8 M for T. cruzi and 44.8 M to 49.6 M for T. brucei rhodesiense. The IC 50 values for the trypanosomes are comparable to those obtained with L. donovani promastigotes, which have previously been shown to be susceptible to artemisinin compounds in vitro and in vivo (1,15,23). Similar results were also obtained in drug IC 50 determinations for Leishmania and Trypanosoma spp.…”
supporting
confidence: 83%
“…Dentre eles, podem ser citados os terpenóides (Yang;Liew, 1992;Camacho et al, 2000), aminoglicosteróides e aminosteróides (Kam et al, 1997), naftoquinonas (Fournet et al, 1992a;Kayser et al, 2000), chalconas (Chen et al, 1993), glicosídios iridóides (Mittal et al, 1998); fl avonóides (Araújo et al, 1998), neolignanas (Barata et al, 2000) e os alcalóides (Mahiou et al, 1994;Fournet et al, 1994;Queiroz et al, 1996;Akendengue et al, 1999).…”
Section: Discussionunclassified
“…Recent studies have demonstrated that artemisinin derivatives are equally potent and efficacious against several other common infectious parasites of man including Toxoplasma gondii (Jones-Brando et al, 2006) which causes toxoplasmosis that is responsible for behavioral abnormalities in patients, Trypanosoma and Schistosoma species (Mishina et al, 2007;Utzinger et al, 2001) that are responsible for human trypanosomiasis or 'sleeping sickness' and schistosomiasis, respectively. Artemisinin derivatives are also effective against some other pathogens including those responsible for cryptosporidiosis, amoebiasis, giardiasis, clonorchiasis and leishmaniasis (Ma et al, 2004;Yang and Liew, 1993). Moreover, artemisinin has been recently indicated as a potential and effective compound against a number of viruses including hepatitis B, C and others (Efferth et al, 2008).…”
Section: Introductionmentioning
confidence: 99%